Perancangan Gim Digital tentang Camilan Tradisional Khas Sulawesi sebagai Media Edukasi untuk Remaja - Thomas, James Riady; Tjandra, Miki; Aryani, Dewi Isma (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Indonesian regional snacks are highly valued for their cultural significance due to their distinctive taste, composition of ingredients, and processing techniques. Due to the globalization of free trade exchange and the ease with which information can be exchanged in the modern technology era, teens' interest in traditional snacks from different parts of Indonesia is currently waning. Especially on the island of Sulawesi, many traditional food vendors have forced to close their doors as a result of the Indonesian people's adaptation to the digital world over the past five years. With the purpose of educating and acquainting teenagers aged 12 to 18 with typical Sulawesi snacks, this mix-method study used a glass box method approach. The design visualization results use a simple chibi cartoon graphic style so that the content in the game may be readily conveyed and understood by the target market, while the data collecting and analysis results use literature studies and questionnaires. Thus, in an effort to maintain the cultural flavor of typical Indonesian snacks, this digital game can be utilized as an instructional tool regarding common Sulawesi snacks.